A Theoretical Study of Dynamic Behavior of Diphenyldisulphide Molecule on Fe Surface: Novel Ultra-Accelerated Quantum Chemical Molecular Dynamics Approach - Akira Endou (Japanese Society of Tribologists, 2008)
We developed a novel ultra-accelerated quantum chemical molecular dynamics simulator and applied it to adsorption dynamics of a diphenyldisulphide molecule on Fe(001) surface. As a result, we observed formation of two Fe-S bonds among the diphenyldisulphide molecule and the Fe(001) surface. In the adsorption state of the molecule on the Fe surface, it was found that two phenyl groups of the molecule were faced parallel to the Fe surface. From the electronic structure analysis, it was clarified that the parallel configuration was induced by the interaction of the 3d atomic orbitals of Fe atoms with the 2p atomic orbitals of carbon atoms as well the formation of Fe-S bonds.